DEVELOPMENT OF EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) BASED CHEMSDRO MOBILE LEARNING FOR INDONESIAN JUNIOR HIGH SCHOOL: RATE OF REACTION - Fibonacci, Anita; Azizati, Zidni; Wahyudi, Tomi (JTK (Jurnal Tadris Kimiya), 2020)
ICT learning media mostly emphasize students content and motivation. The emphasis on protecting the environment as a form of development of sustainable living awareness is often considered not significant. Accordingly, many youth students begin to lose development of sustainable living awareness. This study aimed to produce and evaluate a learning media based on games in Android mobile learning- Chemsdro (Chemistry in Android) oriented to Education for Sustainable Development (ESD) on the topic rate of reaction. Characteristic Â of Chemsdro Learning Media was the topic of rate of reaction created in the form of games that embedded in android mobile phones with game characters who have a mission to protect the environment. This learning tool was designed to give motivation for students to care about the environment. This research was Research and Development model, it was adopted the steps from Thiagarajaan including define, design, develop, and dissemination steps. The subjects of this study were students grade XI of SMA 1 Kendal. The product validation showed that the Chemsdro learning media was a very appropriate category to use with the Aiken V coefficient of 0.9. Student assessment of Chemsdro learning media also showed a good category.